2011
DOI: 10.1002/mame.201100035
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Graphene–PVDF Foam Composites for EMI Shielding

Abstract: Novel foam composites comprising functionalized graphene (f‐G) and polyvinylidene fluoride (PVDF) were prepared and electrical conductivity and electromagnetic interference (EMI) shielding efficiency of the composites with different mass fractions of f‐G have been investigated. The electrical conductivity increases with the increase in concentration of f‐G in insulating PVDF matrix. A dramatic change in the conductivity is observed from 10−16 S · m−1 for insulating PVDF to 10−4 S · m−1 for 0.5 wt.% f‐G reinfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
209
1
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 372 publications
(214 citation statements)
references
References 28 publications
2
209
1
2
Order By: Relevance
“…Theoretically, the higher the decibel level of EMI SE, the less energy is transmitted through the shielding material. [139] This is confirmed by the values of EMI SE and the average data of the transmissivity obtained. Although the main mechanism on all samples is the transmission of the incident radiation, the inclusion of MWCNTs, greatly increases the absorption mechanism of the EMI shielding in the X-band region.…”
Section: Electromagnetic Interference (Emi) Shieldingsupporting
confidence: 72%
“…Theoretically, the higher the decibel level of EMI SE, the less energy is transmitted through the shielding material. [139] This is confirmed by the values of EMI SE and the average data of the transmissivity obtained. Although the main mechanism on all samples is the transmission of the incident radiation, the inclusion of MWCNTs, greatly increases the absorption mechanism of the EMI shielding in the X-band region.…”
Section: Electromagnetic Interference (Emi) Shieldingsupporting
confidence: 72%
“…Kuang et al [18] shows light weight poly(L-Lactic acid)(PLLA)-MWCNT foam achievẽ 23 dB SE value with 2.5 mm thickness at 10 wt% MWCNT loading. Eswaraiah et al [19] reported that PVDF/graphene foam shows EMI SE ~28 dB at 7 wt% functionalized graphene loading. The formation of foam at high filler loading is extremely difficult by traditional foaming methods (e.g., decomposition of chemical foaming agent) [10].…”
Section: Introductionmentioning
confidence: 99%
“…Most electronic devices that work at high frequency, such as wireless telecommunication systems, local area networks, and other communication equipment, often have noise problems due to electromagnetic wave interference (EMI) (Wu & Li, 2011;Eswaraiah et al, 2011). EMI can reduce the performance of these devices.…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, the demand to eliminate EMI has attracted increased interest as a research 888 Absorption Characteristics of the Electromagnetic Wave and Magnetic Properties of the La0.8Ba0.2FexMn½(1-x)Ti½(1-x)O3 (x = 0.1-0.8) Perovskite System topic (Eswaraiah et al, 2011). Introducing materials that can absorb electromagnetic waves is an alternative solution to eliminating EMI effects.…”
Section: Introductionmentioning
confidence: 99%